ChemInform Abstract: Oxetanyl Peptides: Novel Peptidomimetic Modules for Medicinal Chemistry. Issue 7 (29th January 2015) - McLaughlin, Martin; Yazaki, Ryo; Fessard, Thomas C.; Carreira, Erick M.
Abstract Novel peptidomimetics bearing a non‐hydrolyzable oxetanylamine fragment instead of the normal amide bond are synthesized in different ways.